(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
An experiment was carried out with 80 straight run broiler chicks (cobb-500) reared on rice husk and sawdust to know the production efficiency at 5 weeks during summer. A total 80 straight run broiler chicks (cobb-500) were divided into 4 groups and were assigned to 2 treatments i.e. T1 and T2 in which T1 was used rice husk and T2 was used sawdust. Number of birds per replication were 10. Live weight of birds reared on rice husk and sawdust differed significantly at 5th weeks of age (P<0.05). Feed consumption of broiler was significantly higher on sawdust litter than rice husk. Feed conversion ratio and survivability percentages of broiler were statistically non-significant (P>0.05) between the sawdust and rice husk. The cost of litter per bird and cost of litter per kg live weight gain were 14.07% and 20.10% higher in rice husk than sawdust respectively. It is evident from the study that sawdust was more economic than rice husk. Considering all the facts and findings of the study, it can be conducted that live weight and feed consumption of broiler was better in sawdust litter materials than rice husk. Sawdust was also cheaper than rice husk. Therefore, using sawdust as a litter material can lead to better production efficiency and cost savings for broiler farmers during summer. Asian Australas. J. Biosci. Biotechnol. 2023, 8 (2), 17-22